1993
DOI: 10.1093/tropej/39.1.30
|View full text |Cite
|
Sign up to set email alerts
|

Cortisol Levels in Children with Haemoglobinopathies in North Jordan

Abstract: Serum cortisol levels of 100 children 3-10 years old with various haemoglobinopathies were measured. The mean cortisol levels of sickle cell trait, sickle cell disease, beta-thalassemia minor and alpha 2-thalassemia were significantly (P < 0.05) lower than those of normal subjects. The decrease in cortisol levels varied from 25 (in the sickle cell trait group) to 57 per cent (in the alpha 2-thalassemia group) of the mean cortisol levels of the control group. These results suggest the presence of hypoadrenalism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1995
1995
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It was previously shown that Caucasian children release much less cortisol following immunization than Japanese children (4) , and this can explain why decreases of type 1 diabetes occurred in Caucasian children (5) whereas decreases in type 2 diabetes occurred in Japanese children following the discontinuation of the BCG vaccine (6) . In this paper, children from Sardinia, who have a high prevalence of genetic traits or mutations (glucose-6 phosphate dehydrogenase and thalassemia) (7) that lead to decreased cortisol activity (8) , had the lowest levels of childhood obesity but the highest rates of type 1 diabetes in Italy.…”
Section: Resultsmentioning
confidence: 90%
“…It was previously shown that Caucasian children release much less cortisol following immunization than Japanese children (4) , and this can explain why decreases of type 1 diabetes occurred in Caucasian children (5) whereas decreases in type 2 diabetes occurred in Japanese children following the discontinuation of the BCG vaccine (6) . In this paper, children from Sardinia, who have a high prevalence of genetic traits or mutations (glucose-6 phosphate dehydrogenase and thalassemia) (7) that lead to decreased cortisol activity (8) , had the lowest levels of childhood obesity but the highest rates of type 1 diabetes in Italy.…”
Section: Resultsmentioning
confidence: 90%
“…Bashir et al, (Jordan) reported a low cortisol level in 57% of patients with thalassemia with mean cortisol level of 182 ± 32 nmol/L compared with 420 ± 100 nmol/L in control group indicating in vivo hypoadrenalism [17].…”
Section: Discussionmentioning
confidence: 99%
“…[13] Bashir et al, (Jordan) reported a low cortisol level in 57% of patients with thalassemia with mean cortisol level of 182∓32nmol/L compared with 420∓100 nmol/L in control group indicating in vivo hypoadrenalism. [17] In one study of 435 there were 32.5% patients with hypogonadotrophic hypogonadism and reduced pubertal growth spurt stature in 35%, acquired hypothyroidism in 5.9%, hypoparathyroidism in 1.2% and DM in 9.4 %. [5] Delayed puberty and short stature of adrenal insufficiency are common findings but it seems adrenal pituitary axis is almost not affected.…”
Section: Discussionmentioning
confidence: 99%